Peran Kader Posyandu Dalam Mengurangi Angka Stunting Di Desa Tunggak Kecamatan Toroh Kabupaten Grobogan - Wijayanti, Amanda; Winarti; Winduro, Wirid (Solidaritas, 2024)
Posyandu is a basic health service to monitor the growth and development of baluita. In the implementation of posyandu, there are cadres who help. Posyandu cadres play a role in helping optimize the function of posyandu to monitor toddler nutrition so that toddlers do not experience stunting. The purpose of this study is to describe the role of posyandu cadres in reducing stunting rates in Tunggak Village, Toroh District, Grobogan Regency. The focus of this research is the role of posyandu cadres, namely as innovators, pioneers, modernizers and stabilizers. The research method used is qualitative descriptive. Data collection techniques through observation, interviews and documentation. Data analysis techniques use theory from Miles, Huberman (2014). The results showed that the role of posyandu cadres in Tunggak Village, Toroh District, Grobogan Regency was good. The innovator indicator carried out by posyandu cadres are good enough, but there are still gymnastics programs for pregnant women that have not been implemented optimally. The pioneer indicator, cadres have become pioneers of good health but there are still parents of toddlers who do not routinely bring their toddlers to posyandu. Modernizer indicator, the role of posyandu cadres as modernizers is good, cadres are able to utilize technology to provide important information to parents of toddlers. Stabilitator indicator, the role of cadres as stabilizers is good, posyandu cadres have received socialization about stunting handling so that cadres can also socialize it to parents of toddlers to anticipate toddlers being stunted and cadres also monitor the growth and development of toddler nutrition.